Penanaman Nilai-Nilai Pendidikan Karakter dalam Kitab Ta’lim Muta’allim Karya Syekh Az-Zarnuji - Tyas Hidayatulloh; Abdul Hadi; Muhammad Hambal Shafwan (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
The background of this research is that education is a learning process aimed at enhancing intellectual potential by providing it with correct knowledge, but this process also aims at character development efforts. However, education merely turns the seeker of knowledge into a knowledgeable person, without harmonizing it with good morals and ethics. The question raised in this research concerns the cultivation of character education values ??found in the book of thoughts by Sheikh az-Zarnuji, Talimul Muta’alim. The purpose of this research is to identify and investigate the character education values ??written in the book "Ta’lim Muta'alim" according to Sheikh az-Zarnuji's thoughts, and to determine the relationship between these values. Narrowing down the issue, we focus on the character education values ??according to Sheikh as-Zarnuji's thoughts (research on Ta’lim Muta’alim). The results of this research are expected to serve as a reference for understanding character education and be used as reference material for related research in the future. This research is a literature study of the book "Ta’lim Muta’alim" on character education values. Data collection is done through documentation methods, while the data analysis used in this research is the content analysis method. This analysis is used to clarify the content of certain values ??in the book, taking into account its context. The primary data source is the book Ta’lim Muta’alim, while the secondary sources are the translated book Ta’lim Muta’alim, other books, theses, dissertations, and other papers. The results of this research indicate that the character education values ??contained in the book Ta’lim Muta’allim include religious, responsibility, democratic, tolerance, hard work, discipline, independence, appreciation of achievement, love for peace, love for reading, social concern, and curiosity.